POSTERIOR-TO-ANTERIOR COLLATERAL PATHWAY IN BILATERAL INTERNAL CAROTID ARTERY STENOSIS: A CASE REPORT - Permana, Andi; Rakhmatiar, Rodhiyan (Journal of Pain, Headache and Vertigo, 2026)
Introduction: Bilateral internal carotid artery (ICA) stenosis is a rare condition with potential for serious neurological complications. However, sufficient collateral circulation may mitigate clinical manifestations. Case Report: A 75-year-old man presented with progressive discomfort in his left leg and had a history of hypertension and coronary artery disease. The neurological examination revealed deficits in cranial nerves VII and XII, as well as left-sided weakness. Imaging revealed bilateral ICA stenosis with hypoperfusion of anterior and middle cerebral arteries, yet maintained cerebral perfusion via collateral flow from the posterior cerebral arteries (PCA) through the posterior communicating arteries. Digital subtraction angiography confirmed the diagnosis. The patient was managed conservatively with antiplatelet, antihypertensive, and lipid-lowering therapy. He remained neurologically stable during hospitalization. Conclusion: This case highlights a rare collateral configuration in bilateral ICA stenosis. Adequate posterior circulation via the PCA can maintain perfusion to anterior territories, potentially preventing major neurological deficits.